Efficacy of Clostridium butyricum Supplementation Combined with Phototherapy for Neonatal Hyperbilirubinemia: A Systematic Review and Meta-Analysis - Eun-Jin Kim; Ho-Yeon Go; Hyun-Kyung Sung (Microorganisms, 2025)
Neonatal hyperbilirubinemia (NH), which commonly presents as jaundice, affects approximately 60% of term infants and up to 80% of preterm infants within the first week of life. This study aimed to assess the efficacy and safety of Clostridium butyricum (C. butyricum) supplementation combined with phototherapy versus phototherapy alone for the treatment of NH. A systematic search of 11 databases (English, Chinese, and Korean) was conducted from 18 April 2025. Eligible randomized controlled trials (RCTs) compared C. butyricum plus phototherapy with phototherapy alone. Meta-analyses were performed using the mean difference (MD), standardized mean difference (SMD), and risk ratio (RR) with a 95% confidence interval (CIs). Evidence quality was evaluated using the GRADE approach. This review included 20 RCTs of 1054 neonates. Compared to phototherapy alone, C. butyricum supplementation significantly reduced total bilirubin (SMD = −1.54, 95% CI: −2.21 to −0.86), indirect bilirubin (SMD = −2.03, 95% CI: −2.98 to −1.07), and time to jaundice resolution (MD = −1.20 days, 95% CI: −1.66 to −0.75), and was associated with fewer adverse events (RR = 0.40, 95% CI: 0.30 to 0.55) (all p < 0.0001). These findings suggest that C. butyricum may have potential as a supportive adjunct therapy for neonatal hyperbilirubinemia. However, further studies are needed to confirm its efficacy and safety. The protocol is registered in PROSPERO (CRD420251031376).